A new species of Microphotina Beier, 1935 from the southernmost region of Amazonia (Mantodea: Photinaidae) - Lanna, Leonardo Moutinho; Fiat, Lucas Linhares; Herculano, João Felipe; Rivera, Julio; Peloso, Pedro (European Journal of Taxonomy, 2023)
A new species of Microphotina Beier, 1935 (Mantodea: Photinaidae: Microphotinini), Microphotina cristalino sp. nov., is described from Mato Grosso, Brazil based on two male specimens. The new species extended the distribution of Microphotina to the southern limits of the Amazon rainforest, in the Cerrado-Amazônia ecotone. A synthesis of the taxonomy, systematics, natural history, and geographic distribution of Microphotina spp. is provided, along with an updated dichotomous key to species. The hypothesis that Microphotina represents a canopy-dwelling lineage is formulated. The role of praying mantises as flagship species for insect and Amazon conservation is briefly discussed.